Altitude/hypoxic training by Olympic athletes for the enhancement of sea level performance - Wilber, R. L. (Medicina Sportiva, 2013)
At the Olympic level, differences in measurable performance are typically less than 0.5 percent. This helps explain why many contemporary elite endurance athletes in summer and winter sport incorporate some form of altitude/hypoxic training within their year-round training plan, believing that it will provide the "competitive edge" to succeed at the Olympic level. This presentation is made with the following objectives in mind: 1. To review research-based evidence supporting the effect of altitude/hypoxic acclimatization on both hematological and non-hematological markers, including erythrocyte volume, skeletal muscle buffering capacity, hypoxic ventilatory response, and physiological efficiency/economy. 2. To describe the practical application of altitude/hypoxic training as utilized by elite athletes. 3. To discuss the concept of "effective hypoxic dose": how high, how many days, how many hours per day? To examine legal and ethical issues associated with the use of altitude/hypoxic training. Within the context of these objectives, both scientific and anecdotal evidence will be presented relative to the efficacy of several contemporary altitude/hypoxic training models currently used by Olympic-level athletes for the purpose of enhancing performance. These include the three primary altitude/hypoxic training models: 1. live high + train high (LH + TH), 2. live high + train low (LH + TL), and 3. live low + train high (LL + TH). The LH + TL model will be examined in detail and will include its various modifications: natural/terrestrial altitude, simulated altitude via nitrogen dilution or oxygen filtration, and hypobaric normoxia via supplemental oxygen. A somewhat opposite approach to LH + TL is the altitude/hypoxic training strategy of LL + TH (intermittent hypoxic training), and data regarding its efficacy will also be presented.